A coupling model of element-based peridynamics and finite element method for elastic-plastic deformation and fracture analysis. (15th April 2022) - Liu, Shuo; Fang, Guodong; Fu, Maoqing; Yan, Xiangqiao; Meng, Songhe; Liang, Jun
Highlights: The coupling element-based peridynamics and finite element method are developed. The coupling model is proposed to solve the elastic-plastic deformation and failure problems. A reducing elements scheme for EBPD is proposed to improve computational efficiency. The coupling model can eliminate the surface effect in EBPD. Abstract: An element-based peridynamics (EBPD) and finite element method (FEM) coupling model is proposed to solve the elastic-plastic deformation and failure problems. The FEM and EBPD are used in the boundary region and the interior elastic-plastic crack growth region, respectively. A scheme is proposed to improve the computation efficiency of EBPD by deleting the bad quality elements in the horizon of each PD node. EBPD has the non-local stress and non-local strain concepts to conveniently describe the yield stress and equivalent plastic strain, and does not have instability problems. The elastic-plastic computation framework is used in the coupling model solved by the incremental method to calculate the elastic-plastic deformation and failure process. The coupling model can calculate the elastic-plastic problem with the linear and nonlinear hardening laws. A 2D elastic-plastic crack propagation process is also simulated by the proposed coupling model. Graphical abstract: Image, graphical abstract